An Intelligent Site Environment Survey System Platform Based on 'Internet + Database'. Issue 1 (February 2021) - Zhi, Yanli; Xi, Weili; Bi, Tao; Li, Chao
Abstract: Intelligent environment survey system platform integrates Internet, database, geographic information system and other technologies, including PC side web page and mobile side APP. The platform is applied to the site environmental survey and monitoring practice, assisting the site environmental survey and monitoring work, solving the problems of site monitoring and survey data management difficulty, high cost, low efficiency, standardization of work procedures and content, low degree of automation, and improving the site survey work efficiency and quality.